(untitled) (Journal of Education and Development, 2025)
Justification: Latin America is undergoing dizzying changes in virtual education as part of an educational strategy to reach a greater number of students and be able to guarantee access to higher education. Compliance with this strategy has faced difficulties due to the challenges of integrating technology into virtual courses in academic institutions. Main objective: Examine the challenges that teachers face when integrating technology into the teaching of virtual courses in a higher education institution. Methodology: The study design was descriptive-correlational. The selection of the sample was carried out by convenience and included the participation of 140 teachers from a private university in Puerto Rico. Data was collected through a validated questionnaire. Results: The most common challenges that teachers face when offering virtual courses through the integration of technology are linked to the use of free platforms by the university which deletes recorded classes in a limited time (30%) and access to online support services offered by the university (27.1%). The areas of the least difficulty presented by teachers were keyboard management and skills (89.3%) and programming and teacher-student interaction outside of class hours (88.6%). Furthermore, a negative relationship was found between having certifications to offer virtual courses and prior technological education with the use of technology (r = -.525; p < .01). Conclusion: Teachers present a few difficulties in managing technology in virtual courses and this is related to obtaining prior preparation in educational technology. Implications: Having a certification or preparation related to educational technology significantly minimizes the degree of difficulty that teachers may experience in the use of technology in teaching virtual courses.